Understanding patient pathways to Mother and Baby Units: a longitudinal retrospective service evaluation in the UK - Nikolina Jovanović; Žan Lep; Giles Berrisford; Aysegul Dirik; Julia Barber; Bukola Kelani; Olivia Protti (Health and Social Care Delivery Research)
Background Mother and Baby Units are specialised psychiatric facilities for women during and after pregnancy. In the United Kingdom, efforts have been made to expand the Mother and Baby Unit availability and establish care guidelines. However, the accessibility of these services for ethnic minority women remains relatively unexplored despite well-documented disparities. Aims To explore patient pathways to Mother and Baby Units in three UK localities, with a focus on variations in pathways between services and among ethnic groups. Methods This is a three-site, longitudinal retrospective service evaluation conducted in Birmingham, London and Nottingham during a 12-month period (1 January–31 December 2019). Electronic records were accessed to extract data on the type of admission, the referral process and the type of pathway (simple or complex). The simple pathway entailed contact with one clinician/service prior to admission to the Mother and Baby Unit, while the complex pathway involved interactions with two or more clinicians/services before Mother and Baby Unit admission. Data were collected using the adapted World Health Organization Encounter form and were analysed using uni- and multivariable analyses. Results Electronic records from 198 patients were analysed, with participants distributed proportionally across three sites: Birmingham (n = 70, 35.4%), London (n = 62, 31.3%) and Nottingham (n = 66, 33.3%). All Mother and Baby Units were nationally commissioned and received referrals from across England. Most patients were in the post partum period, admitted for the first time through emergency, informal and complex pathways. The average length of admission was 6 weeks. Significant differences in admission characteristics were observed between services. Patients of Asian ethnicity had more emergency admissions compared to those of Black and White ethnicities. Ethnicity was the only significant factor associated with the simple/complex care pathway. After controlling for pathway-level and patient-level factors, Black patients were 6.24 times less likely to experience a complex care pathway than White patients. No evidence was found that patients from the Black ethnic background are detained more often than White patients. Limitations The heterogeneity among categorised ethnic groups, data extracted solely from electronic records without validation through patients’ personal accounts of their care pathways, unanalysed declined referrals and the utilisation of pre-COVID-19 pandemic data. The ethnic composition of the study sample matched that of the UK maternity population in the Nottingham subsample, but Black and Asian populations were over-represented in the Birmingham and London subsamples. Conclusion The study provides valuable insights into patient journeys to Mother and Baby Units, highlighting significant differences between services. It also emphasises the role of ethnicity in care pathways. For example, Black patients were less likely to encounter more than two services before Mother and Baby Unit admission, suggesting either more direct access to specialist care or insufficient community-based interventions. This dual interpretation calls for future research to explore whether pathway differences among ethnic groups result from optimal clinical decision-making or gaps in care provision. Future work Should further examine the role of ethnicity in shaping care pathways; explore the link between care pathway types and treatment outcomes; investigate if simple or complex pathways result from optimal clinical decisions or gaps in the healthcare system and explore admissions to general wards versus Mother and Baby Units and transitions between these units. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number 17/105/14. Plain language summary Mother and Baby Units are special psychiatric facilities designed to provide inpatient care for women dealing with serious mental health problems during pregnancy or after giving birth. In recent years, there have been attempts to improve these services. However, we still do not have much information about how patients get to these units. In this study, we wanted to learn how women reach Mother and Baby Units in the United Kingdom. We studied three different locations: Birmingham, London and Nottingham. We reviewed the electronic records of 198 women who used Mother and Baby Units in these locations during 2019. Here is what we found: Most patients were admitted to the Mother and Baby Unit after giving birth, and they were usually admitted in an emergency. On average, they stayed in the Unit for about 6 weeks. We found differences between services in how patients were admitted, how long they stayed, the reasons they were admitted and how long it took them to reach the Unit. When we looked at what affects a patient’s journey to the Mother and Baby Unit, we found that ethnicity played an important role. For example, more Asian women were admitted in emergencies, and black women went through fewer services before reaching the Unit. The study sheds light on how patients access Mother and Baby Units, showing that the process varies by location. It also found that ethnicity plays a role. For example, black patients had fewer steps to reach the Unit compared to White British patients. This could mean direct access to care or a lack of community-based support. More research is needed to determine whether this is due to clinical decisions or gaps in the care system.